Evaluation of Efficacy of Intense Pulsed Light (IPL) System in the Treatment of Facial Acne Vulgaris:Comparision of Different Pulse Durations; A Pilot Study - Barikbin, Behrooz; Ayatollahi, Azin; Younespour, Shima; Hejazi, Somayeh (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: Adequate control of acne is difficult, regardless of the various conventional modalities. Intense Pulsed Light (IPL) system is one of the emerging options that are become increasingly useful. METHODS: To achieve the best IPL parameters we evaluated the efficacy and tolerability of IPL at 752-nm wavelength, 35 j/cm2 fluence, 55-ms pulse duration in comparison with 572-nm wavelength, 35 j/cm2 fluence, 101-ms pulse duration, in a 5 week, controlled, double-blind, split-face clinical trial. Final assessment was made by comparison of the changes in inflammatory and non-inflammatory acne lesions count and the Acne Global Severity Scale (AGSS) between two groups, based on standardized photography. RESULT: Fifteen female patients, with mean age of 23.53±2.47 years (range 20-28) completed the 5-week therapy period. For both therapies, significant reductions (approximately 30%) in the comedone and inflammatory lesions count were observed (p=0.0024). There was no significant difference in the efficacy of the two treatments in reducing the percentage of comedone and inflammatory lesions count from baseline to 5th week (p=0.76 and p=0.61, respectively). Based on acne global severity scale (AGSS), no significant difference in the severity of acne lesions of the two treatments was observed at 5th-week visit (p=0.26). CONCLUSION: Considering the lack of significant difference between the two treatments and since greater risks are associated with lower pulse duration, the use of longer pulse durations is recommended, especially in darker skin phenotype. Further studies with larger number of patients are required to fully comparison of efficacy of these parameters in IPL systems for acne vulgaris.